Poštna logistika - Lisec, Andrej (University of Maribor Press, 2022)
Logistics in Post. The book deals with postal logistics, where the basic concepts of mail and logistics are given. Through a historical review of the post office, we stop at postal traffic and individual phases. Special emphasis is placed on packages and letters. Finally, the challenges of the post in the field of future development, sustainable development, including the use of drones, are presented.